Geostandards and Geoanalytical Research Bibliographic Review 2016. Issue 4 (8th December 2017) - Weis, Ulrike; Schwager, Beate; Stoll, Brigitte; Nohl, Uwe; Karlowski, Patricia; Leisgang, Isabelle; Zwillich, Florentine; Jochum, Klaus Peter
Key Points: Literature review of nearly 8500 geoanalytical publications. Geochemical and environmental reference materials. 780 selected articles with summaries of target analytes, and relevant reference materials and producers.